Literacy in the English-speaking Caribbean: Some responses to the problems of illiteracy and functional illiteracy - Ellis, Patricia
There has been an increased awareness of the level of literacy and its implications for the region in recent years. As a result, government and nongovernmental institutions have made efforts, both nationally and regionally, to address the inadequate literacy levels. This paper examines the level of illiteracy and functional illiteracy and the efforts and outcomes of various activities/programmes to address the situation. Some insights on the factors critical to the elimination of illiteracy are offered
Keywords: Illiteracy